Early United States experience with liver donation after circulatory determination of death using thoraco‐abdominal normothermic regional perfusion: A multi‐institutional observational study. Issue 6 (11th April 2022) - Sellers, Marty T.; Nassar, Ahmed; Alebrahim, Musab; Sasaki, Kazunari; Lee, David D.; Bohorquez, Humberto; Cannon, Robert M.; Selvaggi, Gennaro; Neidlinger, Nikole; McMaster, William G.; Hoffman, Jordan R.H.; Shah, Ashish S.; et al.
Abstract: Mortality on the liver waitlist remains unacceptably high. Donation after circulatory determination of death (DCD) donors are considered marginal but are a potentially underutilized resource. Thoraco‐abdominal normothermic perfusion (TA‐NRP) in DCD donors might result in higher quality livers and offset waitlist mortality. We retrospectively reviewed outcomes of the first 13 livers transplanted from TA‐NRP donors in the US. Nine centers transplanted livers from eight organ procurement organizations. Median donor age was 25 years; median agonal phase was 13 minutes. Median recipient age was 60 years; median lab MELD score was 21. Three patients (23%) met early allograft dysfunction (EAD) criteria. Three received simultaneous liver‐kidney transplants; neither had EAD nor delayed renal allograft function. One recipient died 186 days post‐transplant from sepsis but had normal presepsis liver function. One patient developed a biliary anastomotic stricture, managed endoscopically; no recipient developed clinical evidence of ischemic cholangiopathy (IC). Twelve of 13 (92%) patients are alive with good liver function at 439 days median follow‐up; one patient has extrahepatic recurrent HCC. TA‐NRP DCD livers in these recipients all functioned well, particularly with respect to IC, and provide a valuable option to decrease deaths on the waiting list.